Experience as a Barrier to Contestability in Airline Markets - Baker, Samuel H.; Pratt, James B. (The Review of Economics and Statistics, 1989)
Contrary to one of the predictions of the contestability hypothesis, price in deregulated U.S. passenger airline markets is related to actual competition from diversifying former intrastates and newly established carriers. More important, former intrastates have a larger impact on price than do newly established firms–a result consistent with these markets being imperfectly competitive because of an industry experience barrier to entry. Unlike actual competition, a measure of potential competition has no effect in constraining price. Copyright 1989 by MIT Press.